Early-stage product development in small technology-based start-up enterprises : a thesis presented in partial fulfilment of the requirements for the degree of Master of Engineering in Product Development at Massey University, Albany, New Zealand - Sidwell, Kit (Massey University, 2012)
Success in New Product Development can be elusive even to companies that are well financed, experienced in methodology, and in possession of a seemingly promising concept. In a small start-up business, often all the entrepreneur has to begin with is an exciting prospect, an idea for a product, but little in the way of direction and funding with which to make it a reality. Yet small companies in New Zealand and Australia are regularly attempting to enter markets with products that are often highly innovative and with great potential for growth. With this in mind, research into early-stage product development in small, technology based start-up enterprises was undertaken, with the aim of exposing key management aspects that influence the path that is taken. The overall research problem for this study is therefore: How do start-up enterprises undertake the early stages of technology-based Product Development? Several important areas of focus were established through a review of the literature, in order to target the research in a manner that could provide valuable theory building on the topic. The research questions addressed in this study are: RQ 1: What elements of NPD best practices can be adopted by start-up technology-based enterprises when developing new products? RQ 2: What are the critical success factors and enablers for New Product Development in start-up technology-based enterprises? RQ 3: What barriers to NPD are specific to Tech-start-up enterprises in New Zealand/Australia? A qualitative research framework was used to investigate these focus areas, carried out under a multiple case study methodology. The research questions and literature review guided development of exploratory interview questions, which were put to the director/ entrepreneur of 8 start-up companies in New Zealand and Australia. The major themes observed were associated with addressing the needs of the market, collaboration, flexibility of the development process, as well as other management methodologies and tactics. This study concludes that early-stage product development in start-up technology based enterprises is an exercise in adaptive project management, in that each unique development requires a tailored approach in order to achieve the overall goal of a well-targeted product.
Keywords: New products; High technology industries; New business enterprises; Small business